Analisis Kinerja Bank Umum Dengan Menggunakan Metode Rating Bank Berbasis Resiko - Alodia Islamey Dagna; Efrizal Syofyan (Jurnal Eksplorasi Akuntansi, 2020)
This study intend to analyze the financial performance of State-Owned Commercial Banks (BUMN) during the period 2014-2018 with the RBBR (Risk Based Bank Rating) manner. The research method used to analyze the financial performance of BUMN banks is a descriptive method with a quantitative approach. The results showed that the overall financial soundness of BUMN banks since the 2013 until 2015 period from the risk profile factor analysis showed that BUMN NPL located in healthy condition and from the LDR side of BUMN banks were in sanely healthy condition. As for the factor of Good Corporate Governance (GCG) in general, BUMN Banks have managed and implemented GCG well. For earnings factors calculated by the ROA and NIM ratios as a whole, BUMN Banks are in very healthy condition. The evaluation of the capital factor using the CAR Ratio shows that all BUMN banks are in very healthy condition.